2020
DOI: 10.3390/foods9111705
|View full text |Cite
|
Sign up to set email alerts
|

Use of Almond Skins to Improve Nutritional and Functional Properties of Biscuits: An Example of Upcycling

Abstract: Upcycling food industry by-products has become a topic of interest within the framework of the circular economy, to minimize environmental impact and the waste of resources. This research aimed at verifying the effectiveness of using almond skins, a by-product of the confectionery industry, in the preparation of functional biscuits with improved nutritional properties. Almond skins were added at 10 g/100 g (AS10) and 20 g/100 g (AS20) to a wheat flour basis. The protein content was not influenced, whereas lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
3
45
0
Order By: Relevance
“…However, its conditions of cultivation associated to the high cost of its importation as well as the phenomenon of gluten intolerance have led to the development of several researches in order to find alternatives to wheat. Nowadays, researches are directed towards the use of local raw materials due to their composition which will improve the nutritional composition of biscuits and also to their great potential for improving the sustainability of food systems [ 5 ]. In this light, the promotion of the use of composite flours, which integrate flours derived from local crops (cereals, tubers, roots, and leguminous seeds), in bakery products such as biscuits is being encouraged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its conditions of cultivation associated to the high cost of its importation as well as the phenomenon of gluten intolerance have led to the development of several researches in order to find alternatives to wheat. Nowadays, researches are directed towards the use of local raw materials due to their composition which will improve the nutritional composition of biscuits and also to their great potential for improving the sustainability of food systems [ 5 ]. In this light, the promotion of the use of composite flours, which integrate flours derived from local crops (cereals, tubers, roots, and leguminous seeds), in bakery products such as biscuits is being encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…Besides rice, other local ingredients for which a growing attention is paid nowadays in biscuit formulation are those rich in health-promoting compounds. Pasqualone et al [ 5 ] demonstrated the use of almond skins rich in bioactive compounds in the formulation of nutritious and functional biscuits. Safou ( D. edulis (L.)) a highly perishable local food [ 11 ] stands as an example of those ingredients which can be valorized in the preparation of functional biscuits for improving its sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the addition of almond skin (at 10 g/100 g and 20 g/100 g) to a wheat flour basis for biscuit preparation indicated an increase in antioxidant potential [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional properties of cookies can be enhanced throughout fortification using additional health-beneficial ingredients (e.g. protein isolates and fibre) (Jan et al, 2018;Pasqualone et al, 2020;Boukid, Rosell, & Castellari, 2021) or replacement of the basic ingredients (wheat flour, sugar and fat) by healthier alternatives such as protein-rich flours (e.g. pulses flours), low-calorie sweeteners and rich unsaturated fats (Aggarwal, Sabikhi, & Sathish Kumar, 2016;Thongram et al, 2016;Curti et al, 2018;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%